Identitas Sosial Influencer Berhijab di Media Sosial - Fitri, Susanti Ainul; Labibah Nursyabani, Siti Azkia (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
The aim of this study is to analyze how the hijab is upheld as a religious symbol and a marker of self-identity, social identity, and to understand the commodification process of the hijab in the fashion industry. It also seeks to examine the role of the hijab as a symbol of cultural identity and the interaction between culture, religious traditions, and modernity in the representation of the hijab on social media. This research employs a qualitative approach using case study methods. The findings indicate that the hijab, as a religious symbol, has evolved into an identity marker that blends spiritual values with a modern lifestyle within the social media space. Hijab-wearing influencers on social media have positioned the hijab as a modern lifestyle trend and a form of fashion expression. Female hijab influencers on social media represent the hijab not only as a religious or lifestyle symbol but also as part of a broader cultural evolution that integrates religious values, local culture, and modernity.